KEWAJIBAN AYAH TERHADAP ANAK AKIBAT TERJADINYA PERCERAIAN YANG HAK NAFKAH TIDAK DIMINTA DAN TIDAK DITETAPKAN DALAM PUTUSAN HAKIM (PUTUSAN NOMOR 496/PDT.G/2022/PA.KTP) - NIM. A1012191078, ALFIAN DARUSSALAM (Jurnal Fatwa Hukum, 2025)
Abstract In the divorce trial process between the Plaintiff and the Defendant, the Panel of Judges has made efforts to reconcile the two parties through mediation stages as regulated in the applicable laws and regulations. However, the mediation efforts did not produce results because each party remained adamant in their decision to divorce, the development of the trial, the Plaintiff changed his petitum and requested to be given custody of the two children. The Defendant did not object to the change in the request and stated his agreement to the custody request submitted by the Plaintiff. This change in petitum is an important part of the case examination process because it concerns the best interests of the child, which must be the main consideration in every decision related to child custody in divorce cases. Therefore, the formulation of the problem in this study is as follows: "What are the Father's Obligations Regarding Child Support Rights Due to Divorce in Decision Number 496 / PDT.G / 2022 / PA.KTP?". The type of research the author will use is normative research. In other words, it is research conducted on actual conditions or real situations that have occurred in society with the aim of understanding and discovering the facts and data needed to address the gap between das sollen das sein (the gap between theoretical conditions and legal factors). Therefore, it is concluded that under Indonesian law, a father's obligation to provide child support remains morally and legally obligatory, regardless of whether the child support is requested or determined by a judge's decision. This is due to the inherent obligation: The legal consequences of the obligation to provide child support are a fundamental responsibility inherent in a father's status (whether in marriage or after divorce) and are not waived simply by the absence of a request or court decision. This obligation continues until the child reaches adulthood or becomes independent. Legal sanctions: A father's obligation to provide child support if the judge's decision regarding the right to child support is not requested or determined by the judge, as the provision of child support in a divorce decision does not relieve the father of his financial responsibilities. Indonesian law prioritizes child protection, so the obligation to provide child support remains in effect and can be pursued through legal channels at any time. The purpose of this research is to analyze the father's obligations to children whose child support is not requested or determined by the judge's decision and to analyze the legal consequences for fathers who fail to provide child support if the judge's decision regarding the right to child support is not requested or determined by the judge. Keywords: Divorce, Decision, Child Support, Responsibility, Father's Obligations Abstrak Dalam proses persidangan perkara perceraian antara Penggugat dan Tergugat, Majelis Hakim telah melakukan upaya untuk mendamaikan kedua belah pihak melalui tahapan mediasi sebagaimana diatur dalam peraturan perundang-undangan yang berlaku. Namun, upaya mediasi tersebut tidak membuahkan hasil karena masing-masing pihak tetap bersikukuh pada keputusannya untuk bercerai, pperkembangan persidangan, Penggugat mengubah petitumnya dan memohon untuk diberikan hak asuh atas kedua anak tersebut. Tergugat tidak menyatakan keberatan atas perubahan permohonan tersebut dan menyatakan persetujuannya terhadap permohonan hak asuh yang diajukan oleh Penggugat. Perubahan petitum ini menjadi bagian penting dalam proses pemeriksaan perkara karena menyangkut kepentingan terbaik bagi anak, yang harus menjadi pertimbangan utama dalam setiap putusan yang berkaitan dengan hak asuh anak dalam perkara perceraian. Maka maka rumusan masalah dalam penelitian ini ialah sebagai berikut :“Bagaimanakah Kewajiban Ayah Terhadap Hak Nafkah Anak Akibat Terjadinya Perceraian Dalam Putusan Nomor 496/PDT.G/2022/PA.KTP?”. Jenis Penelitian yang akan digunakan oleh penulis adalah penelitian normatif. Dengan kata lain yaitu suatu penelitian yang dilakukan terhadap keadaan sebenarnya atau keadaan nyata yang telah terjadi di masyarakat dengan maksud mengetahui dan menemukan fakta-fakta dan data yang dibutuhkan dari adanya kesenjangan antara das sollen das sein yaitu kesenjangan antara keadaan teoritis dengan faktor hukum. Maka disimpulkan bahwa secara hukum di Indonesia, kewajiban ayah untuk menafkahi anak tetap wajib ada secara moral dan hukum, terlepas dari apakah nafkah tersebut diminta atau sudah ditetapkan dalam putusan hakim, karena Kewajiban Melekat: Akibat hukum kewajiban memberi nafkah merupakan tanggung jawab mendasar yang melekat pada status seorang ayah (baik dalam ikatan pernikahan maupun setelah bercerai) dan tidak gugur hanya karena tidak ada permintaan atau putusan pengadilan. Kewajiban ini berlangsung hingga anak menjadi dewasa atau mandiri dan Sanksi Hukum: Kewajiban ayah yang tidak memberikan nafkah jika putusan hakim mengenai hak nafkah tidak diminta dan tidak ditetapkan oleh hakim, karena nafkah dalam putusan cerai tidak membebaskan ayah dari tanggung jawab finansialnya. Hukum Indonesia memprioritaskan perlindungan anak, sehingga kewajiban nafkah tetap berlaku dan dapat dituntut melalui jalur hukum kapan saja. Dengan tujuan penelitian menganalisis kewajiban Ayah terhadap anak yang nafkahnya tidak diminta dan tidak ditetapkan dalam putusan hakim dan menganalisis Akibat Hukum Bagi Ayah Yang Tidak Memberikan Nafkah Jika Putusan Hakim Mengenai Hak Nafkah Tidak Diminta Dan Tidak Ditetapkan Oleh Hakim Kata Kunci : Perceraian, Putusan, Nafkah, Tanggung Jawab, Kewajiban Ayah